MEDIATION AS A SKILL IN FOREIGN LANGUAGE CLASSES IN SECONDARY EDUCATION - Žindžiuvienė, Ingrida Egle (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Although the importance of mediation tasks was introduced in Common European Framework of Reference for Languages: Learning, teaching, assessment (CEFR) in 2001, the development of mediation skills was finally legitimized in the recent edition of CEFR (Council of Europe, 2020). However, the development of this “fifth” language skill during the language classes remains a problematic issue: contrary to the other four language skills (reading, writing, speaking and listening), teachers often face the dilemma of how and when to introduce mediation activities and to what extent mediation should be applied in the process of foreign language teaching and learning. The aim of the research is to survey language teaching policies in Lithuania, Latvia and other EU countries from the aspect of the development of mediation skills in language classes in secondary education. Teaching programs of the English language in senior classes of the secondary school are surveyed from the aspect of mediation skills as defined in the newest edition of CEFR. The research results show that mediation activities are still not adequately included in foreign language classes: first of all, language syllabuses must be adjusted to the revised edition of CEFR. The research has proved the necessity of mediation skills to be included in the secondary education programs of foreign languages. Therefore, the selection of textbooks used in senior classes of foreign languages in secondary education must follow the recommendations outlined in CEFR, where the development of mediation skills is especially emphasized due to the present needs. It has been determined that mediation activities can develop students’ multilingual and plurilingual skills and raise students’ awareness of the peculiarities of both the native language and the foreign one.